Peran Kualitas Auditor dalam Meningkatkan Relevansi Nilai di dalam Earnings dan Book Value of Equity - Christopher Bryan; Daniel Firmansyah; Rinanigsih Rinanigsih; Johan Yanto (Universitas Prasetiya Mulya, 2019)
The purpose of this research is to see the difference of value relevance contained in earnings and book value of equity to stock return on companies audited by different audit quality. Audit quality measurements are measured using auditor size and auditor specialization. The sample used in the study is a company listed on the Indonesia Stock Exchange between the periods 2006 to 2015, the company engaged in non-financial, possess the completeness of the financial report during period of study, and has no negative book value of equity. The study used paired t-test for each subsample. The results of this study indicate that there is no difference in the value relevance of the audited companies with different audit quality.